Sketching Structural Lightness: Frei Otto and the Treehouses (1959-1987) (diségno, 2026)
Frei Otto’s treehouse projects offer his vision through their detailed drawings and unbuilt architecture’s structure hybrids. These works echo the ecological and anatomical analogies proposed by Philip Steadman, underscoring the deep connection between the built environment and natural systems. The concept of the ‘treehouse’ or Baumhäuser, and its intrinsic relationship with architecture and nature, was a consistent theme in Otto’s work from 1959 to 1989. The treehouse is a timeless architectural idea, found across cultures and centuries from Papua New Guinea to modern designs by Baumraum studio. These structures blend structural design, nature, and spatial adaptability. The objective of this research focus in Otto’s ‘treehouse’ concept through four key case studies from New York to Berlin. It begins by examining interviews, drawings and literature on his philosophy, tracing the concept’s evolution from early unbuilt proposals to the Ökohaus in Tiergarten. This project, the most comprehensive built expression of these principles, was studied via fieldwork and drawing analysis to understand its materialization. Otto’s earlier works –including watercolours, sketches, and experimental models–demonstrate his interest in architecture rooted in the genius loci and a holistic ecological vision. His treehouse projects exemplify a synthesis of form, construction, and environmental awareness, an approach that remains pertinent to contemporary architectural discourse.
Keywords: Frei Otto; treehouse; ecological architecture; Ökohaus; architectural drawings